Determination of Cadmium in Blood of Iranians Zinc Mine Workers - Mohajeri, E.; Moattar, F. (Asian Journal of Chemistry, 2010)
Toxic metal cadmium is playing the major role in environmental health threats and appear to be seriously affecting the mine workers' health. In the present study, the concentration of toxic heavy element cadmium in zinc mine worker's blood was determined. Flameless atomic absorption spectrometery were used for cadmium measurment. The results indicated that the concentration of cadmium in blood is more than the standard value recommended by WHO found in 100 % of the workers. It causes several diseases in most of the workers. The average concentration of cadmium in the blood samples in this study is found to be 6.2 μg/L.